Optical Inspection System for Gear Tooth Surfaces Using a Projection Moiré Method - Yi-Cheng Chen; Jr-Yi Chen (Sensors, 2019)
The demand for rapid online optical inspection of gear tooth surfaces is increasing, especially for precision gears. In this study, a non-contact optical measurement method was established for the inspection of gear tooth surfaces. For the system architecture, a halogen lamp was selected as the light source, and a collimated beam was produced by an autocollimator. Subsequently, moiré fringes were formed as the collimated beam went through the two linear gratings. The moiré fringes projected on the gear tooth surface were recorded with a charge-coupled device (CCD) camera, and the contour of the gear tooth surface was estimated and reconstructed from the phase information of the fringes by our developed computer codes. To verify the accuracy of the system, a spur gear tooth surface measured by a commercial coordinate measuring machine (CMM) was defined as the reference tooth profile. The tooth topography, involute profile deviation, and axial-direction deviation were successfully calculated by measuring the deviation of the optically measured surface based on the reference gear tooth profiles measured using the CMM.